Pregnancy Outcome in COVID 19 Infected Patients: In a COVID Dedicated Hospital of Chattogram, Bangladesh - Chowdhury, Fahmida Islam; Shirin, Fahmida; Sultana, Nahid; Ara, Sarwat; Sultana, Munawar; Deb, Aporna; Amin Chowdhury, Muhammad Jabed Bin; Chowdhury, Shanaj Jahan; Karim, Tanjila; Ferdous, Jannatul; et al. (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Corona Virus Disease (COVID-19) a pandemic has become a global health concern. Pregnant women are at an increased risk due to physiologic changes in their immune, cardiopulmonary and coagulation systems. This study was designed to evaluate the fetomaternal outcome of the pregnant patients with COVID-19. Materials and methods: This cross-sectional type of observational study was conducted in Obstetric and Gynecology Department of Chittagong Medical College Hospital from July 2021 to September 2021. Total 51 hospitalized pregnant patients with confirmed COVID-19 were enrolled. Relevant data were recorded in a preformed data collection sheet and analyzed by SPSS version 26. Results: Total patients were 51 with a mean age of 28 years, 73.5% patients were in third trimester, 35.3% were in >37 weeks of gestation . Common symptoms were fever( 33.3%), cough (19.6%) and respiratory distress(29.4%). There were two maternal deaths who were treated in ICU. There were 2 spontaneous abortions. 69.23% underwent caesarean section, 30.77% underwent Normal Vaginal Delivery (NVD) 9.8% patients underwent premature termination of pregnancy. Ongoing pregnancy were 19 (37.3%). There were 17 live births and 3 Intrauterine Deaths (IUD) and 2 neonatal deaths. Among the mothers, 29(56.8%) had no associated complications, 19.65% had Preeclampsia and 5.9% had Gestational Diabetes Mellitus. About 10 babies had birth weight less than 2.5 kg and were transferred to NICU. Conclusion: During this study, it was found that pregnancy outcome was not good in COVID positive pregnant women . For the infected mothers early medical supervision and availability of ICU in critical condition is needed for better pregnancy outcome. JCMCTA 2021 ; 32 (2) : 95-99